Determinan Penerapan SAK EMKM dan Implikasinya terhadap Kualitas Laporan Keuangan UMKM Kuliner di Kabupaten Tangerang - Maman Sulaeman; Aning Fitriana (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2026)
The low level of adoption of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) among MSMEs in Indonesia has resulted in poor financial reporting quality and limited access to financing. This study aims to analyze the factors influencing the level of SAK EMKM implementation and its impact on the quality of financial statements among culinary MSMEs in Tangerang Regency. The study employs a quantitative approach using a survey method involving 404 culinary MSME respondents. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that understanding of SAK EMKM has a positive effect on the level of SAK EMKM implementation (path coefficient 0.357). Perceived benefits have a positive effect on the level of SAK EMKM implementation (path coefficient 0.291). Business scale also has a positive effect on the level of SAK EMKM implementation (path coefficient 0.277). Furthermore, the level of SAK EMKM implementation has a positive effect on the quality of financial statements (path coefficient 0.652). The research model explains 59.1% of the variance in the level of SAK EMKM implementation and 42.5% of the variance in financial reporting quality. The study concludes that understanding, perceived benefits, and business scale are important factors driving the adoption of SAK EMKM, and that the implementation of these standards contributes significantly to improving the quality of financial statements among culinary MSMEs